Analisis Kebutuhan Evaluasi Pembelajaran Unsur Dalam Tari Merak Bagi Peserta Didik Sekolah Menengah Pertama Berbasis Crossword Puzzle - Ani Nur Auliyatun Latifah; Wahyu Lestari (Jurnal Sitakara, 2024)
This research to create innovative learning in creative evaluation through a crossword puzzle. The problem is focused on the fact that teachers still use conventional or paper-based learning evaluation models. To approach this issue, Sugiyono's theory on Evaluation is used as a reference for conducting the research. The learning evaluation process was carried out at SMP IT INSAN CENDEKIA to analyze the needs of students and teachers in the learning evaluation process at the school. The research method used is Research and Development (R&D), which will produce an online-based learning evaluation innovation. Data was collected through qualitative research used to capture art learning evaluation assessment data conducted by teachers using observation, interviews, and documentation data collection techniques. The data was analyzed descriptively qualitatively. Quantitative research was used to test the validity and reliability of the products to be produced. The results of the research show that the wordwall puzzle is very practical for use by students of SMP IT INSAN CENDEKIA in the learning evaluation process, with 22 out of 24 students able to understand and use this application effectively. This study concludes that the online-based crossword puzzle learning evaluation model can provide new innovations in the evaluation process and has a high level of effectiveness and efficiency.